Prevalence of gastrointestinal symptoms and related drug use among pregnant women of South-Western Nigeria - Jemilohun, Abiodun Christopher; Fasanu, Adeniyi Olanipekun; Tijani, Aramide Mikhail; Stanley, Olayinka Gbenga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Gastrointestinal (GI) symptoms are quite common in pregnancy but there is paucity of data in regard to their frequencies in the south-western part of Nigeria. This study was conducted to determine the prevalence of various gastrointestinal symptoms and related drug use among south-western Nigerian women. Methods: A cross-sectional multicenter study involving three centers in two states of south-western Nigeria from March to August 2014. A composite questionnaire consisting of demographic data, anthropometric indices, obstetrics information, a list of gastrointestinal symptoms and drug usage was administered to 420 consecutive healthy pregnant women at various gestational ages. Data were analysed and presented as means ±S.D, frequencies and percentages. Relationships between categorical variables were explored with chi-square test. A 5% significance level (p < 0.05) was considered significant. Results: Respondents had age range of 18-43years and a mean of 27.26 (±4.98). The commonest gastrointestinal symptom was nausea (46.9%), followed by vomiting (45.0%) and then anorexia (36.2%). Excessive salivation, heart burn, constipation, regurgitation, and bloating had frequencies of 35.5%, 28.3%, 20.7%, 19.0% and 18.3% respectively. Epigastric pain was the least frequent among the symptoms (16.9%).The association between the parity of respondents and each of the GI symptoms was not statistically significant. But associations between educational status and excessive salivation and anorexia were statistically significant (P-value of 0.018 and 0.023 respectively). Subjects with heartburn had the highest drug usage (23.5%), followed by those with vomiting (22.8%). Subjects with excessive salivation (2%) had the least drug intake. Conclusions: Gastrointestinal symptoms are common among pregnant women of south-western Nigeria. There is need for the physician to be abreast with the prevalence of the common pregnancy related GI problems in the particular locality of practice and the appropriate way to manage them.